A Channel Network Model as a Framework for Characterizing Variably Saturated Flow in Biofilm‐Affected Soils. Issue 2 (2nd May 2013) - Rosenzweig, Ravid; Furman, Alex; Shavit, Uri
Abstract : Understanding and predicting the hydraulic properties of biofilm‐affected porous media is of high importance in bioremediation, filtration, and bioreactors. In this study, a channel network model was applied for characterizing the variably saturated flow in biofilm‐affected soils. The soil pores are represented by a network of interconnected channels having a triangular cross‐section in which the shape of the water surface is determined by the matric head. The channel network model provides a better representation of the pore space than the capillary bundle model by accounting for pore connectivity and allowing for dual occupancy at individual pores. The effect of the biofilm on the network hydraulic properties was analyzed by considering three synthetic scenarios for the biofilm spatial distribution. The first scenario assumed that the biofilms fully clogged the smallest pores; the second scenario assumed that the biofilm covered all pore walls in a layer of uniform thickness; and the third scenario assumed that the biofilm covered a uniform fraction of the pore cross‐sectional area. We showed that the biofilm spatial distribution has a significant effect on the flow and hydraulic properties. Moreover, pore connectivity plays a significant role when considering flow in biofilm‐affected soils and therefore must be taken into account. Finally, the simulations demonstrated that the effect of biofilms on the hydraulic properties of the network is a complicated and nonlinear function that depends not only on the biofilm scenario but also on the saturation.